Comparison of key concepts on education expenditure between the UOE framework and national accounts framework (Publications Office of the European Union, 2023)
This working paper makes an inventory of the main conceptual differences between the methodology for the collection of data on expenditure on education in the UNESCO-UIS/OECD/EUROSTAT data collection on education statistics (the UOE data collection) and national accounts statistics compiled according to the ESA 2010. The aim of the inventory of the conceptual differences is to support statisticians to use national accounts data when compiling UOE data returns and to support users wishing to relate the education expenditure data from the UOE and national accounts aggregates. In this working paper, UOE definitions are examined (geographical scope, accounting principles, scope of education, sources of funds, educational institutions) before being compared to concepts in the ESA 2010. A theoretical analysis of how UOE expenditure transactions would map to ESA transactions is also offered, as well as more practical comparisons between UOE amounts for education expenditure and similar national accounts aggregates.
10.2785/265072
Keywords: Graue Literatur; Amtliche Publikation; Bildungsfinanzierung; Erhebungstechnik; Volkswirtschaftliche Gesamtrechnung; Bildungsstatistik; Vergleich; EU-Staaten; education statistics; education costs; data collection; EU statistics; statistical method; public expenditure; comparative analysis; user guide